Business Licensing Obligations for E-Commerce under Government Regulation No. 80/2019 - Achmad Haekal; Sudarsono; Shinta Hadiyantina (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
This study examines the discrepancy between das sollen and das sein regarding the obligation to register a business license as mandated in Article 15(1) of Government Regulation Number 80 of 2019. Although the regulation requires all business actors to register their licenses with the Central Government, its implementation in Malang City remains ineffective. Of approximately 85,200 MSMEs, only about 22,000 had obtained official licenses by 2024. The study addresses two issues: (1) the factors contributing to the low compliance of micro-enterprise actors with licensing requirements, and (2) the legal implications for those operating without a business license. Using a socio-legal method with a juridical-sociological approach, the research relies on primary and secondary data collected through fieldwork and literature study. The sample consists of 13 respondents and 2 key informants, analyzed qualitatively. The findings reveal that the main cause of ineffective implementation is the low level of legal awareness and knowledge among micro-enterprise actors. Eight respondents were unaware of the obligation to register with the Disnaker PMPTSP of Malang City, while five respondents were aware but had not complied. This demonstrates that regulatory implementation has not been optimal. The legal implications for non-compliant business actors include the loss of legal validity of their operations and the potential imposition of administrative sanctions under applicable laws.